The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40104-022-00786-0
|View full text |Cite
|
Sign up to set email alerts
|

Production systems and important antimicrobial resistant-pathogenic bacteria in poultry: a review

Abstract: Economic losses and market constraints caused by bacterial diseases such as colibacillosis due to avian pathogenic Escherichia coli and necrotic enteritis due to Clostridium perfringens remain major problems for poultry producers, despite substantial efforts in prevention and control. Antibiotics have been used not only for the treatment and prevention of such diseases, but also for growth promotion. Consequently, these practices have been linked to the selection and spread of antimicrobial resistant bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 193 publications
0
12
0
Order By: Relevance
“…To ensure productivity and maintain animal welfare, mitigation of the emergence and spread of bacterial disease is essential [ 37 ]. Current management strategies focus on biosecurity, vaccines, and nutritional supplements [ 64 ]. As such, a considerable market gap exists for non-antibiotic microbiota modulators that do not promote clinically relevant antimicrobial resistance and positively aid in growth promotion of food animals such as prebiotics, probiotics, essential oils, and organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure productivity and maintain animal welfare, mitigation of the emergence and spread of bacterial disease is essential [ 37 ]. Current management strategies focus on biosecurity, vaccines, and nutritional supplements [ 64 ]. As such, a considerable market gap exists for non-antibiotic microbiota modulators that do not promote clinically relevant antimicrobial resistance and positively aid in growth promotion of food animals such as prebiotics, probiotics, essential oils, and organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella pneumoniae has been documented to be a widely widespread pathogenic agent with a high prevalence of antimicrobial resistance, however antibiotic sensitivity of Klebsiella pneumoniae has not been thoroughly researched, particularly in poultry [ 41 ]. In vitro, antibiotic susceptibility assays were performed on 30 isolated Klebsiella pneumoniae in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To contribute to identifying issues and opportunities in developing efficient and safe production practices, major poultry production systems and their impacts on AMR have been reviewed [ 57 ]. It has been reported that different diets could contribute to the transmission of ARGs by remodeling the intestinal environment, which could affect exogenous ARGs to change the intestinal resistome [ 58 ].…”
Section: Discussionmentioning
confidence: 99%